2016
DOI: 10.1192/bjp.bp.114.157123
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for adults with bipolar disorder: systematic review and meta-analysis

Abstract: There is evidence that psychological interventions are effective for people with bipolar disorder. Much of the evidence was of low or very low quality thereby limiting our conclusions. Further research should identify the most effective (and cost-effective) interventions for each phase of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 91 publications
(216 reference statements)
2
90
1
6
Order By: Relevance
“…These programmes, the Barcelona BDs Program77 (21 sessions over 6 months) and the Life Goals Program78 (phase I is six weekly sessions), also have tools to aid implementation with workbooks and handout materials, and both are first‐line psychoeducational interventions based on level 2 evidence for the prevention of relapse. Individual psychoeducation based on these manuals would probably be effective, and when individual trials utilizing several different approaches to psychoeducation are combined in a meta‐analysis, individual psychoeducation of at least five sessions would still be a first‐line intervention for relapse prevention, based on level 2 evidence 75, 79, 80. One large study demonstrated that the six‐session Life Goals Program psychoeducational intervention was equivalent in relapse prevention to 20 sessions of individual CBT, at far lower cost,81 with probable shared mechanisms 82.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…These programmes, the Barcelona BDs Program77 (21 sessions over 6 months) and the Life Goals Program78 (phase I is six weekly sessions), also have tools to aid implementation with workbooks and handout materials, and both are first‐line psychoeducational interventions based on level 2 evidence for the prevention of relapse. Individual psychoeducation based on these manuals would probably be effective, and when individual trials utilizing several different approaches to psychoeducation are combined in a meta‐analysis, individual psychoeducation of at least five sessions would still be a first‐line intervention for relapse prevention, based on level 2 evidence 75, 79, 80. One large study demonstrated that the six‐session Life Goals Program psychoeducational intervention was equivalent in relapse prevention to 20 sessions of individual CBT, at far lower cost,81 with probable shared mechanisms 82.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…9) seemed to be outliers compared to other RCTs of individual or group psychoeducation versus either treatment as usual or attentional controls (14). The evidence was reported as weak or very weak with few pre-registered large multicentre blinded RCTs conducted independently of the developers of the intervention (1,14,15). Few studies controlled for the variation in outcome due to natural history of bipolar disorder e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Existing systematic reviews and meta-analyses were searched for further papers (Justo et al, 2007;Oud et al, 2016;Reinares et al, 2016;Yesufu-Udechuku et al, 2015). Reviews were identified from the electronic searches and through searching the Cochrane database.…”
Section: Search Strategymentioning
confidence: 99%